2020
DOI: 10.1002/cam4.2976
|View full text |Cite
|
Sign up to set email alerts
|

TIGIT enhances CD4+ regulatory T‐cell response and mediates immune suppression in a murine ovarian cancer model

Abstract: Ovarian cancer (OC) is the fifth‐leading cause of cancer‐related death in women with a pathogenesis involving activation of regulatory T cells (Tregs). The T‐cell immunoglobulin and ITIM domain (TIGIT) is a well‐known immune checkpoint molecule that inhibits T‐cell responses. However, the role of TIGIT in OC is not comprehensively understood. In this study, we revealed crucial functions of TIGIT in the development and progression of OC. ID8 cells were used to establish a murine OC model. TIGIT expression was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…41 Chen et al demonstrated that TIGIT, a well-known immune checkpoint, could enhance CD4+ regulatory T cell responses and mediate immunosuppression in a murine OC model. 42 Meanwhile, the presence of CD8+ TILs was correlated with a favorable prognosis in patients with epithelial OC. 43 Interestingly, our results showed that CD4+ T cells were positively correlated with FAM83D, and CD8+ T cells were negatively correlated with FAM83D.…”
Section: Dovepressmentioning
confidence: 98%
“…41 Chen et al demonstrated that TIGIT, a well-known immune checkpoint, could enhance CD4+ regulatory T cell responses and mediate immunosuppression in a murine OC model. 42 Meanwhile, the presence of CD8+ TILs was correlated with a favorable prognosis in patients with epithelial OC. 43 Interestingly, our results showed that CD4+ T cells were positively correlated with FAM83D, and CD8+ T cells were negatively correlated with FAM83D.…”
Section: Dovepressmentioning
confidence: 98%
“…Perhaps the mEER HPV-positive HNSCC model has a higher frequency or abundance of TIGIT on Tregs than the Tgfbr1/Pten double knockout model of HPV-negative HNSCC. Intratumoral Treg depletion has been reported with several anti-TIGIT antibodies (e.g., the CT26 colon model) (41,53,54), due to higher Fc affinity for FcyR and stronger induction of ADCC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TIGIT regulates Treg function. As mentioned above, Tregs are superior in suppressing T cell activation, and anti-TIGIT treatment reduces the proportion of CD4+ Tregs and inhibits the suppressive ability of Tregs [39][40][41][42], suggesting another pathway for cancer immunotherapy.…”
Section: Effect Of Tigit On T Cells In Preclinical Trialsmentioning
confidence: 93%